A kind of drawing decorative film and its preparation method and application in furniture

By setting a protective layer composed of Ellostone nanotubes and PBT/PETG composite film on the aluminum plated layer, the problem of insufficient heat resistance of the aluminum plated layer of the brushed decorative film is solved, and higher heat resistance, wear resistance and mechanical properties are achieved, and suitable for use in different environments.

CN119193021BActive Publication Date: 2025-04-08HEYUAN WANLI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411327304.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-04-08
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The aluminum-plated layer of the existing brushed decorative films is insufficient in heat resistance and is prone to thermal deformation. The brushed film base material such as PET has limitations in wear resistance and heat resistance.

Method used

A protective layer is provided on the aluminum-plated layer. The protective layer is composed of Elosite nanotubes (HNTs) and PBT/PETG composite film. By integrating HNTs into acrylic resin and coating onto the surface of the PBT/PETG composite film, the formed protective layer improves the heat resistance, wear resistance and mechanical properties of the material.

Benefits of technology

The heat resistance, wear resistance and mechanical properties of the brushed decorative film are improved, and its use stability and durability in different environments are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193021B_ABST
    Figure CN119193021B_ABST
Patent Text Reader

Abstract

The present invention relates to a drawing decorative film and a preparation method thereof and application in furniture, belonging to the technical field of decorative films. The decorative film comprises: a protective layer, a first bonding layer, an aluminum-plated layer, a PET drawing film, a second bonding layer and a release film in sequence; wherein the protective layer is obtained by first integrating halloysite nanotubes (HNTs) into an acrylic resin, and then coating it on the surface of a PBT / PETG composite film and curing it, and the base of the protective layer is a composite film of PBT / PETG. This composite material has the advantages of both PBT and PETG; HNTs can improve the heat resistance of the material; the silane coupling agent and anionic surfactant added in the process of integrating HNTs into the acrylic resin are used to improve the compatibility of HNTs in the acrylic resin, thereby enhancing the interfacial compatibility and mechanical properties of the material. Therefore, the protective layer of the present invention can provide the overall decorative film with water-resistant, heat-resistant and wear-resistant protective effects, has good practicality, and can be used as a protective film for furniture to provide protection for furniture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of decorative films, and in particular to a drawing decorative film and a preparation method thereof and application in furniture. Background Art

[0002] Brushed decorative film is a new type of decorative film material developed in the past decade. As a product surface decoration, brushed decorative film imitates the texture of metal surface, giving people a visual effect of metallic texture. Through the brushing process, the decorative film can show a unique luster and enhance the decorative effect. Compared with traditional metal materials, brushed decorative film usually has good flexibility and is easy to process and install.

[0003] Generally, an aluminum coating is set in the brushed decorative film to improve the glossiness and appearance texture of the brushed film. However, the aluminum coating is sensitive to temperature and has insufficient heat resistance to withstand the radiation heat of the evaporation source and the condensation heat of the evaporated product, so it is easy to be thermally deformed, affecting the coating quality. In addition, the brushed film base of the brushed decorative film is usually made of plastic materials such as PET, which may have certain limitations in wear resistance and heat resistance compared to metal materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a drawing decorative film having the advantages of wear resistance, heat resistance and high strength, a preparation method thereof and an application in furniture.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a brushed decorative film, which comprises: a protective layer, a first adhesive layer, an aluminum-plated layer, a PET brushed film, a second adhesive layer and a release film in sequence; wherein the protective layer is a composite film of halloysite nanotubes (HNTs) and PBT / PETG, and the preparation method of the protective layer comprises the following steps:

[0007] S1, adding PBT and PETG into a twin-screw extruder for uniform plasticization and extrusion molding to obtain a PBT / PETG composite film; wherein the mass ratio of PBT to PETG is 1: (1-5);

[0008] S2, first placing tetraethoxysilane in an acid solution for hydrolysis reaction, then adding anionic surfactant, halloysite nanotubes and acrylic resin, and mixing to obtain a mixed coating; wherein the hydrolysis reaction temperature is 70-80° C., the hydrolysis reaction time is 5-10 min, the mass ratio of halloysite nanotubes to anionic surfactant is 1:(15-25), and the mass ratio of acrylic resin, halloysite nanotubes and tetraethoxysilane is 1:(0.1-0.3):(1-2);

[0009] S3, coating the mixed coating on the surface of the PBT / PETG composite film, and obtaining the protective layer after curing.

[0010] The present invention arranges an aluminum coating layer before the PET wire drawing film, which gives the PET wire drawing film a metallic luster, improves the appearance texture and decorative effect of the product, and makes it more attractive in packaging and decorative applications. The anti-oxidation property of the aluminum layer is combined with the chemical stability of PET, providing good corrosion resistance, making the PET wire drawing film more suitable for use in various environments. However, the aluminum coating layer has poor heat resistance and is prone to thermal deformation, thereby affecting the wire drawing effect and the coating quality. Therefore, a protective layer is arranged on the aluminum coating layer to improve the wear resistance, water resistance and mechanical properties of the product.

[0011] The protective layer of the present invention is obtained by first integrating HNTs into acrylic resin, and then coating it on the surface of PBT / PETG composite film and curing it. HNTs have high thermal stability and begin to degrade at about 400°C, so the presence of HNTs can improve the heat resistance of the material. After HNTs are added to the acid solution, the HNTs are acidified and have hydroxyl groups on the surface, which provide active sites for subsequent tetraethoxysilane grafting, and can form stable chemical bonds with acrylic resin through tetraethoxysilane. Moreover, tetraethoxysilane (TEOS) is hydrolyzed under acidic conditions to produce silanol groups (Si-OH). The Si-OH generated by TEOS hydrolysis can react with the hydroxyl or carboxyl functional groups on the surface of the acidified HNTs to form covalent bonds or hydrogen bonds, thereby realizing the combination of TEOS and HNTs, which helps to improve the dispersibility of HNTs in acrylic resin and avoid the aggregation of HNTs, thereby obtaining a more uniform composite material. This combination can enhance the interfacial compatibility and mechanical properties of the material, and can further improve the compatibility of HNTs and acrylic resin and enhance the performance of the composite material.

[0012] HNTs (halloysite nanotubes) have a unique nanotubular structure, with the inner cavity and outer surface carrying opposite charges, the inner cavity surface carrying a positive charge, and the outer surface carrying a negative charge. This property allows HNTs to adsorb anionic surfactants through the positive charge in their lumen, forming a hydrophilic coating on the surface of HNTs, increasing the wettability of HNTs in acrylic resin, and helping HNTs to be better dispersed in acrylic resin to form a uniform suspension and avoid precipitation. This enhances the interfacial bonding between HNTs and acrylic resin and improves the overall water resistance of the composite material.

[0013] The substrate of the protective layer is a composite film of PBT / PETG, and the solubility parameters of PBT and PETG are similar, so there is good compatibility between them, and this compatibility helps to improve the overall performance and stability of the decorative film. PBT is an engineering plastic with excellent comprehensive performance, but the thermal conductivity of pure PBT is relatively low, that is, the heat resistance is insufficient. PETG is a non-crystalline copolyester with good viscosity, transparency, color, chemical resistance and stress whitening resistance. When PBT and PETG are compounded, the high transparency and good impact strength of PETG can be utilized to improve the performance of PBT, the addition of PBT can improve the toughness and impact resistance of PETG, and the addition of PETG can improve the heat resistance and processing properties of PBT, so this composite material has the advantages of PBT and PETG. In the extrusion molding process, at high temperature, PBT and PETG undergo a certain degree of ester exchange reaction in situ to generate copolymers, and these copolymers serve as interface compatibilizers, so that the material maintains good mechanical properties, and PETG can improve the toughness of the material simultaneously. So the protective layer of the present invention can provide water-resistant and wear-resistant protective effects for the overall decorative film.

[0014] Preferably, the anionic surfactant is sodium olefin sulfonate.

[0015] Preferably, the mass ratio of the acid solution to tetraethoxysilane is (3-4):1.

[0016] Preferably, the acid solution is an acetic acid solution, and the mass concentration of the acetic acid solution is 20-30wt%.

[0017] More preferably, the mass ratio of PBT to PETG in the PBT / PETG composite film is 1:2.

[0018] Preferably, in the method for preparing the protective layer, the extrusion temperature is 220-245°C and the extrusion time is 5-10 minutes. More preferably, the extrusion temperature is 230-240°C.

[0019] Preferably, in step S2 of the method for preparing the protective layer, the mixing temperature is 45-55° C. and the mixing time is 10-30 min.

[0020] Preferably, the protective layer has a thickness of 50-60 μm.

[0021] Preferably, the thickness of the first adhesive layer is 5-10 μm.

[0022] Preferably, the second adhesive layer has a thickness of 5-10 μm.

[0023] Preferably, the thickness of the PET drawing film is 40-50 μm.

[0024] Preferably, the thickness of the aluminum plating layer is 100-300 nm.

[0025] Preferably, the brushed decorative film has a thickness of 1 to 5 mm.

[0026] In a second aspect, the present invention provides a method for preparing the brushed decorative film, comprising the following steps:

[0027] (1) Vapor-depositing an aluminum layer on the surface of the PET drawing film;

[0028] (2) applying an adhesive between the protective layer and the aluminum-plated layer, and curing the adhesive to obtain a first bonding layer;

[0029] (3) The adhesive is coated between the PET brushed film and the release film, and a second bonding layer is obtained after curing, and the layers are compounded to obtain the brushed decorative film.

[0030] Preferably, in steps (2) and (3), the curing temperature is 80-90° C. and the curing time is 1-2 hours.

[0031] Preferably, the preparation method of the PET brushed film comprises the following steps: using a transfer mold with brushed patterns to apply UV glue to the PET film, and performing UV light curing and embossing to obtain the PET brushed film.

[0032] Preferably, the adhesives used in the first adhesive layer and the second adhesive layer are both acrylic resin adhesives.

[0033] In a third aspect, the present invention provides the use of the brushed decorative film in preparing a furniture protective film. The brushed decorative film can be covered on the surface of furniture, and in addition to providing a brushed decorative effect, it can also provide the furniture with water resistance and wear resistance, and it has good adhesion to the furniture surface and strong durability.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention arranges an aluminum-plated layer before the PET brushed film, which gives the PET brushed film a metallic luster and improves the appearance texture and decorative effect of the product. However, in order to solve the problem that the aluminum-plated layer has poor heat resistance and is prone to thermal deformation, a protective layer is arranged on the aluminum-plated layer to improve the wear resistance, heat resistance, water resistance and mechanical properties of the product. The protective layer of the invention is obtained by first integrating HNTs into acrylic resin, and then coating the acrylic resin onto the surface of a PBT / PETG composite film and then curing the composite film. The base of the protective layer is a PBT / PETG composite film. When PBT is composited with PETG, the high transparency and good impact strength of PETG can be used to improve the performance of PBT, so the addition of PETG can improve the toughness and impact performance of PBT, and the addition of PBT can improve the heat resistance and processing performance of PETG. The composite material has the advantages of both PBT and PETG. HNTs have high thermal stability and begin to degrade at about 400°C, so the presence of HNTs can improve the heat resistance of the material. The silane coupling agent and anionic surfactant added in the process of integrating HNTs into the acrylic resin are used to improve the compatibility of HNTs in the acrylic resin, thereby enhancing the interface compatibility and mechanical properties of the material, and can further improve the compatibility of HNTs with the acrylic resin, thereby enhancing the performance of the composite material. Therefore, the protective layer of the present invention can provide the overall decorative film with water-resistant, heat-resistant and wear-resistant protective effects, has good practicality, and can be used as a protective film for furniture to provide protection for the furniture. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic structural diagram of the wire drawing decorative film of the present invention;

[0037] Figure 2 This is a physical picture of the brushed decorative film of the present invention;

[0038] Figure 1 Middle: 1. Protective layer; 2. First bonding layer; 3. Aluminum-plated layer; 4. PET brushed film; 5. Second bonding layer; 6. Release film. DETAILED DESCRIPTION

[0039] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0040] The sources of materials, reagents and equipment used in the following examples and comparative examples are as follows:

[0041] PBT: manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number is P909269, Purity: medium viscosity injection grade, MI: 18-22g / 10min (225℃);

[0042] PETG: The manufacturer is China Resources Chemical Materials Technology Co., Ltd., the brand is CR-5531;

[0043] Halloysite nanotubes: manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., brand number 103763;

[0044] Tetraethoxysilane: manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., brand: T110593;

[0045] Sodium olefin sulfonate: α-sodium olefin sulfonate solution, manufactured by Shanghai MacLean Biochemical Technology Co., Ltd., brand S875355, purity: 35% aqueous solution;

[0046] Acrylic resin: The manufacturer is Guangdong Kelisen Resin Co., Ltd., brand name KN5560;

[0047] Acrylic resin adhesive:

[0048] A. The manufacturer is Shanghai Weikai Optoelectronic New Materials Co., Ltd., and the brand is SA850;

[0049] B. The manufacturer is British Permabond, the brand is TA430;

[0050] PET film: The manufacturer is Dongguan Hongmei New Materials Co., Ltd., and the model is transparent PET film;

[0051] UV glue: The manufacturer is Dongguan Gaotu New Materials Co., Ltd., brand name is GT3315;

[0052] Release film: The manufacturer is Suzhou Mei'erlun New Material Technology Co., Ltd., brand number is 10A;

[0053] Abrasion tester: The manufacturer is Shanghai Tianchen Modern Environmental Technology Co., Ltd., the brand is JM-V;

[0054] Pencil hardness tester: The manufacturer is Suzhou Science Instrument Co., Ltd., and the brand is BYK PH-5800.

[0055] Unless otherwise specified, other materials, reagents, and equipment used in the examples and comparative examples can be obtained from commercial sources.

[0056] Example 1

[0057] A brushed decorative film comprises in sequence: a protective layer 1, a first adhesive layer 2, an aluminum-plated layer 3, a PET brushed film 4, a second adhesive layer 5 and a release film 6; the thickness of the protective layer 1 is 55 μm, the thickness of the first adhesive layer 2 is 6 μm, the thickness of the second adhesive layer 5 is 10 μm, the thickness of the PET brushed film 4 is 45 μm, the thickness of the aluminum-plated layer 3 is 200 nm, and the thickness of the brushed decorative film is 3 mm.

[0058] The method for preparing the protective layer 1 comprises the following steps:

[0059] S1. First, PBT and PETG are added into a twin-screw extruder for uniform plasticization and extrusion molding to obtain a PBT / PETG composite film; wherein the mass ratio of PBT to PETG is 1:2, the extrusion temperature is 230°C, and the extrusion time is 7 minutes;

[0060] S2, firstly hydrolyze tetraethoxysilane in a 25wt% acetic acid solution with a mass concentration of 3 times its mass at 75°C for 6min, then add sodium olefin sulfonate, halloysite nanotubes and acrylic resin, and stir and mix at 50°C for 20min to obtain a mixed coating; wherein the mass ratio of halloysite nanotubes to sodium olefin sulfonate is 1:20, and the mass ratio of acrylic resin, halloysite nanotubes to tetraethoxysilane is 1:0.2:1.5;

[0061] S3, coating the mixed coating on the surface of the PBT / PETG composite film, and obtaining the protective layer 1 after curing.

[0062] The method for preparing the brushed decorative film comprises the following steps:

[0063] (1) UV glue is applied to the PET film using a transfer mold with a brushed pattern, and the PET brushed film 4 is obtained by UV light curing and embossing. The PET brushed film 4 is then placed in a vacuum evaporation machine to make the vacuum degree in the coating chamber reach 1.3×10 -2 Pa, heating high-purity aluminum wire to 1300°C to melt and evaporate it into gaseous state, the aluminum wire is continuously melted and evaporated on the evaporation boat, and gaseous aluminum particles are deposited and cooled on the surface of the moving PET drawing film 4 to form a continuous and bright metal aluminum layer, thereby obtaining the aluminum-plated layer 3;

[0064] (2) coating an acrylic resin adhesive A between the protective layer 1 and the aluminum-plated layer 3, and curing at 85° C. for 1 h to obtain a first bonding layer 2;

[0065] (3) The acrylic resin adhesive A is coated between the PET drawing film 4 and the release film 6, and cured at 85° C. for 1 h to obtain the second adhesive layer 5, and the layers are compounded to obtain the drawing decorative film.

[0066] Example 2

[0067] A brushed decorative film comprises in sequence: a protective layer 1, a first adhesive layer 2, an aluminum-plated layer 3, a PET brushed film 4, a second adhesive layer 5 and a release film 6; the thickness of the protective layer 1 is 55 μm, the thickness of the first adhesive layer 2 is 6 μm, the thickness of the second adhesive layer 5 is 10 μm, the thickness of the PET brushed film 4 is 45 μm, the thickness of the aluminum-plated layer 3 is 200 nm, and the thickness of the brushed decorative film is 3 mm.

[0068] The method for preparing the protective layer 1 comprises the following steps:

[0069] S1. First, PBT and PETG are added into a twin-screw extruder for uniform plasticization and extrusion molding to obtain a PBT / PETG composite film; wherein the mass ratio of PBT to PETG is 1:3, the extrusion temperature is 220°C, and the extrusion time is 10 minutes;

[0070] S2, firstly hydrolyze tetraethoxysilane in a 20wt% acetic acid solution of 4 times its mass at 70°C for 10min, then add sodium olefin sulfonate, halloysite nanotubes and acrylic resin, and stir and mix at 45°C for 30min to obtain a mixed coating; wherein the mass ratio of halloysite nanotubes to sodium olefin sulfonate is 1:15, and the mass ratio of acrylic resin, halloysite nanotubes to tetraethoxysilane is 1:0.1:1;

[0071] S3, coating the mixed coating on the surface of the PBT / PETG composite film, and obtaining the protective layer 1 after curing.

[0072] The method for preparing the brushed decorative film comprises the following steps:

[0073] (1) UV glue is applied to the PET film using a transfer mold with a brushed pattern, and the PET brushed film 4 is obtained by UV light curing and embossing. The PET brushed film 4 is then placed in a vacuum evaporation machine to make the vacuum degree in the coating chamber reach 1.3×10 -2 Pa, heating high-purity aluminum wire to 1300°C to melt and evaporate it into gaseous state, the aluminum wire is continuously melted and evaporated on the evaporation boat, and gaseous aluminum particles are deposited and cooled on the surface of the moving PET drawing film 4 to form a continuous and bright metal aluminum layer, thereby obtaining the aluminum-plated layer 3;

[0074] (2) coating an acrylic resin adhesive A between the protective layer 1 and the aluminum-plated layer 3, and curing at 80° C. for 2 h to obtain a first bonding layer 2;

[0075] (3) The acrylic resin adhesive A is coated between the PET drawing film 4 and the release film 6, and cured at 80° C. for 2 h to obtain the second adhesive layer 5, and the layers are compounded to obtain the drawing decorative film.

[0076] Example 3

[0077] A brushed decorative film comprises, in sequence: a protective layer 1, a first adhesive layer 2, an aluminum-plated layer 3, a PET brushed film 4, a second adhesive layer 5 and a release film 6; the thickness of the protective layer 1 is 55 μm, the thickness of the first adhesive layer 2 is 6 μm, the thickness of the second adhesive layer 5 is 10 μm, the thickness of the PET brushed film 4 is 45 μm, the thickness of the aluminum-plated layer 3 is 200 nm, and the thickness of the brushed decorative film is 3 mm.

[0078] The method for preparing the protective layer 1 comprises the following steps:

[0079] S1. First, PBT and PETG are added into a twin-screw extruder for uniform plasticization and extrusion molding to obtain a PBT / PETG composite film; wherein the mass ratio of PBT to PETG is 1:3, the extrusion temperature is 245°C, and the extrusion time is 5 minutes;

[0080] S2, firstly hydrolyze tetraethoxysilane in a 30wt% acetic acid solution of 4 times its mass at 80°C for 5min, then add sodium olefin sulfonate, halloysite nanotubes and acrylic resin, and stir and mix at 55°C for 10min to obtain a mixed coating; wherein the mass ratio of halloysite nanotubes to sodium olefin sulfonate is 1:25, and the mass ratio of acrylic resin, halloysite nanotubes to tetraethoxysilane is 1:0.3:2;

[0081] S3, coating the mixed coating on the surface of the PBT / PETG composite film, and obtaining the protective layer 1 after curing.

[0082] The method for preparing the brushed decorative film comprises the following steps:

[0083] (1) UV glue is applied to the PET film using a transfer mold with a brushed pattern, and the PET brushed film 4 is obtained by UV light curing and embossing. The PET brushed film 4 is then placed in a vacuum evaporation machine to make the vacuum degree in the coating chamber reach 1.3×10 -2 Pa, heating high-purity aluminum wire to 1300°C to melt and evaporate it into gaseous state, the aluminum wire is continuously melted and evaporated on the evaporation boat, and gaseous aluminum particles are deposited and cooled on the surface of the moving PET drawing film 4 to form a continuous and bright metal aluminum layer, thereby obtaining the aluminum-plated layer 3;

[0084] (2) coating an acrylic resin adhesive B between the protective layer 1 and the aluminum-plated layer 3, and curing at 90° C. for 1 h to obtain a first bonding layer 2;

[0085] (3) The acrylic resin adhesive B is coated between the PET drawing film 4 and the release film 6, and cured at 90° C. for 1 h to obtain the second adhesive layer 5, and the layers are compounded to obtain the drawing decorative film.

[0086] Example 4

[0087] The difference between Example 4 and Example 1 is that the mass ratio of PBT to PETG is 1:5.

[0088] Example 5

[0089] The difference between Example 5 and Example 1 is that the mass ratio of PBT to PETG is 1:4.

[0090] Example 6

[0091] The difference between Example 6 and Example 1 is that the mass ratio of PBT to PETG is 1:3.

[0092] Example 7

[0093] The difference between Example 7 and Example 1 is that the mass ratio of PBT to PETG is 1:1.

[0094] Comparative Example 1

[0095] The difference between Comparative Example 1 and Example 1 is that: in Comparative Example 1, no halloysite nanotubes are added.

[0096] Comparative Example 2

[0097] The difference between Comparative Example 2 and Example 1 is that no acetic acid solution is added in step S2 of the method for preparing the protective layer 1 in Comparative Example 2.

[0098] Comparative Example 3

[0099] The difference between Comparative Example 3 and Example 1 is that in the method for preparing the protective layer 1 of Comparative Example 3, sodium olefin sulfonate is not added in step S2.

[0100] Comparative Example 4

[0101] The difference between Comparative Example 4 and Example 1 is that tetraethoxysilane is not added in step S2 of the method for preparing the protective layer 1 in Comparative Example 4.

[0102] Comparative Example 5

[0103] The difference between Comparative Example 5 and Example 1 is that PETG is not added to the protective layer 1 of Comparative Example 5.

[0104] Comparative Example 6

[0105] The difference between Comparative Example 6 and Example 1 is that PBT is not added to the protective layer 1 of Comparative Example 6.

[0106] Comparative Example 7

[0107] The difference between Comparative Example 7 and Example 1 is that the mass ratio of the halloysite nanotubes to the sodium olefin sulfonate in Comparative Example 7 is 1:14.

[0108] Comparative Example 8

[0109] The difference between Comparative Example 8 and Example 1 is that the mass ratio of the halloysite nanotubes to the sodium olefin sulfonate in Comparative Example 8 is 1:26.

[0110] Comparative Example 9

[0111] The difference between Comparative Example 9 and Example 1 is that the mass ratio of acrylic resin:HNTs:tetraethoxysilane in Comparative Example 9 is 1:0.2:0.5.

[0112] Comparative Example 10

[0113] The difference between Comparative Example 10 and Example 1 is that the mass ratio of acrylic resin:HNTs:tetraethoxysilane in Comparative Example 10 is 1:0.2:2.5.

[0114] Performance Testing

[0115] 1. Moisture and heat resistance test: According to GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", the size of each group of samples was cut to 230±5mm in length and 230±5mm in width. The specific test method is: insert the specimen into the specimen clamp and place it in a temperature-controlled water tank filled with boiling distilled water. The specimens and the bottom and wall of the water tank are at least 15mm apart. During the boiling water immersion process, the specimen should always be immersed in boiling water. After 120 minutes of boiling water immersion, take out the specimen clamp and immediately put it into a constant temperature water tank filled with (23±2)℃ distilled water. The liquid level exceeds the specimen and cool for 20 minutes. Take out the specimen from the water and wipe off the water stains on the surface with absorbent gauze. Under natural light, use normal vision (including correction) to observe whether there is bubbling and stratification. The specific surface quality and edge quality ratings are shown in Table 1, and the test data are shown in Table 2.

[0116]

[0117]

[0118] 2. Abrasion resistance test: The abrasion tester was used according to GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method". The turntable speed was 70 rpm, the counterweight was 250 g, and the abrasion tester grinding wheel specifications were The number of turns was set to 100 and the mass wear was recorded. See Table 2 for details.

[0119] 3. Heat resistance test: According to GB / T17657-2022 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the size of each sample is cut into 30mm in length and 20mm in width, and each group of samples is placed in a blast drying oven and dried at 120℃ for 2h. After taking out, observe whether the surface of the sample has cracks and other changes, and record them. Then take it out and dry it at 150℃ for 2h. After taking it out, observe whether the surface of the sample has cracks and other changes, and record them. See Table 2 for details. If cracking or falling off occurs, it is marked as ×, and if there is no cracking or falling off, it is marked as √.

[0120] 4. Hardness test: Use a pencil hardness tester that meets the requirements of GB / T 6736-2006 to scratch the surface of the decorative film. The hardness is expressed by pencil hardness. See Table 2 for details.

[0121] Table 2 Data of each group of samples

[0122]

[0123]

[0124] It can be seen from Table 2 that the decorative films of Examples 1 to 7 all have good heat resistance, water resistance and hardness, especially Example 1.

[0125] Embodiment 1 and embodiment 4-7 mainly explore the influence of the mass ratio between PBT and PETG on product performance. According to the data, the addition of PETG can improve the toughness and impact performance of PBT, and the addition of PBT can improve the heat resistance and processing performance of PETG. More preferably, when the mass ratio between PBT and PETG is 1:3, its heat resistance and hardness are both optimal.

[0126] In Comparative Example 1, no halloysite nanotubes are added, and its heat resistance and water resistance are significantly reduced. This is because the halloysite nanotubes themselves have good thermal stability, and their inner cavity and outer surface have opposite charges, the inner cavity surface has a positive charge, and the outer surface has a negative charge. This property allows HNTs to adsorb sodium olefin sulfonate through the positive charge in their lumen. Sodium olefin sulfonate forms a hydrophilic coating on the surface of HNTs, which improves the wettability of HNTs, enhances the interfacial bonding between HNTs and acrylic resin, and improves the overall water resistance of the composite material.

[0127] In Comparative Example 2, acetic acid is not added, that is, tetraethoxysilane cannot be hydrolyzed and HNTs cannot be activated to obtain hydroxyl groups, so its heat resistance and water resistance are also greatly reduced, indicating that after the acid treatment of HNTs, the surface has hydroxyl groups, which provides active sites for the subsequent tetraethoxysilane grafting, and can form a stable chemical bond with the acrylic resin through tetraethoxysilane. Tetraethoxysilane is hydrolyzed under acidic conditions to produce silanol groups (Si-OH). The Si-OH generated by the hydrolysis of TEOS can react with the hydroxyl or carboxyl functional groups on the surface of the acidified HNTs to form covalent bonds or hydrogen bonds, thereby realizing the combination of TEOS and HNTs, which enhances the interface compatibility and mechanical properties of the material, and can further improve the compatibility of HNTs with acrylic resin and enhance the performance of the composite material.

[0128] In Comparative Example 3, no anionic surfactant is added. Due to the lack of a hydrophilic coating formed on the surface of HNTs by sodium olefin sulfonate, the binding force between HNTs and acrylic resin is reduced, thereby affecting the water resistance, heat resistance and hardness of the decorative film.

[0129] In Comparative Example 4, tetraethoxysilane is not added because tetraethoxysilane is a silane coupling agent. Its absence will make it difficult for HNTs to be grafted onto acrylic resin, so HNTs will aggregate on the acrylic resin and the compatibility will be poor. Therefore, adding tetraethoxysilane can enhance the interface compatibility and mechanical properties of the material, and can further improve the compatibility of HNTs with acrylic resin and enhance the performance of the composite material.

[0130] Comparative Examples 5 and 6 are protective layers 1 whose bases are only PETG and PBT, respectively, and their water resistance, heat resistance and hardness are all reduced, indicating that the composite of PETG and PBT can significantly improve its water resistance and hardness, especially water resistance. It shows that the composite of PETG and PBT solves the defect of PBT being easily deformed by heat.

[0131] In Comparative Example 7, the amount of sodium olefin sulfonate added is too low, and it is difficult for sodium olefin sulfonate to form a uniform hydrophilic coating on HNTs, so HNTs are easily agglomerated in acrylic resin, affecting the binding force between the two, thereby reducing the water resistance, heat resistance and hardness of the product. In Comparative Example 8, the amount of sodium olefin sulfonate added is too low, and the wettability of HNTs is too high. Although HNTs and acrylic resin are more easily dispersed and mixed in water, the material is more likely to absorb water, thereby reducing its water resistance. Therefore, the present invention limits the mass ratio of halloysite nanotubes to anionic surfactants to 1: (15-25), so that the wettability and water resistance of the material are balanced, and the wettability of HNTs in acrylic resin and solution can be improved to improve the compactness of the cross-linked network to achieve water resistance and heat resistance, while the water resistance will not be reduced due to excessive wettability.

[0132] In Comparative Example 9, the amount of tetraethoxysilane added was too low, and it could not react with HNTs in sufficient amount. HNTs aggregated in the acrylic resin, and it was difficult to obtain a uniform coating. In addition, the mechanical properties of the material lacking tetraethoxysilane were also significantly reduced. In Comparative Example 10, the amount of tetraethoxysilane added was too high, resulting in a decrease in the density of the acrylic resin network, thereby affecting the water resistance and heat resistance of the final product.

[0133] In summary, the protective layer 1 of the present invention can provide water-resistant and wear-resistant protection for the overall decorative film. The brushed decorative film can be covered on the surface of furniture. In addition to providing a brushed decorative effect, it can also provide water resistance and wear resistance for the furniture, and it has good adhesion to the furniture surface and strong durability.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A brushed decorative film, characterized in that: Including in order: A protective layer, a first bonding layer, an aluminum-plated layer, a PET brushed film, a second bonding layer and a release film; wherein the protective layer is a composite film of halloysite nanotubes and PBT / PETG, and the preparation method of the protective layer comprises the following steps: S1, adding PBT and PETG into a twin-screw extruder for uniform plasticization and extrusion molding to obtain a PBT / PETG composite film; wherein the mass ratio of PBT to PETG is 1: (1-5); S2. First, tetraethoxysilane is placed in an acid solution for hydrolysis reaction, and then an anionic surfactant, halloysite nanotubes and acrylic resin are added and mixed to obtain a mixed coating; wherein the hydrolysis reaction temperature is 70-80°C, the hydrolysis reaction time is 5-10 min, the mass ratio of halloysite nanotubes to anionic surfactant is 1:(15-25), and the mass ratio of acrylic resin, halloysite nanotubes and tetraethoxysilane is 1:(0.1-0.3):(1-2); S3, coating the mixed coating on the surface of the PBT / PETG composite film, and obtaining the protective layer after curing.

2. The brushed decorative film according to claim 1, characterized in that: The material of the protective layer is selected from at least one of (I) to (III): (I) the anionic surfactant is sodium olefin sulfonate; (II) the mass ratio of the acid solution to tetraethoxysilane is (3-4):1; (III) The acid solution is an acetic acid solution, and the mass concentration of the acetic acid solution is 20-30wt%.

3. The brushed decorative film according to claim 1, characterized in that: In step S1 of the method for preparing the protective layer, the extrusion temperature is 220-245° C. and the extrusion time is 5-10 min.

4. The brushed decorative film according to claim 1, characterized in that: In step S2 of the method for preparing the protective layer, the mixing temperature is 45-55° C. and the mixing time is 10-30 min.

5. The brushed decorative film according to claim 1, characterized in that: The parameters of the brushed decorative film are selected from at least one of (I) to (IV): (I) The thickness of the protective layer is 50-60 μm; (II) the thickness of the first adhesive layer is 5-10 μm; (III) the thickness of the second adhesive layer is 5-10 μm; (IV) The thickness of the PET drawing film is 40-50 μm.

6. The brushed decorative film according to claim 1, characterized in that: The thickness of the brushed decorative film is 1-5 mm.

7. The method for preparing the brushed decorative film according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Evaporating an aluminum layer on the surface of the PET drawing film; (2) applying an adhesive between the protective layer and the aluminum-plated layer, and obtaining a first bonding layer after curing; (3) The adhesive is coated between the PET brushed film and the release film, and a second bonding layer is obtained after curing, and the layers are compounded to obtain the brushed decorative film.

8. The method for preparing a brushed decorative film according to claim 7, characterized in that: In the steps (2) and (3), the curing temperature is 80-90° C. and the curing time is 1-2 hours.

9. The method for preparing a brushed decorative film according to claim 7, characterized in that: The preparation method of the PET drawing film comprises the following steps: using a transfer mold with drawing patterns to apply UV glue to the PET film, and performing UV light curing and embossing to obtain the PET drawing film.

10. Use of the brushed decorative film according to any one of claims 1 to 6 in preparing furniture protective films.

Citation Information

Patent Citations

  • Reversal wire-drawing hot stamping film and preparation method thereof

    CN107399177A

  • Halloysite nanotube-loaded surfactant / conductive polypyrrole composite antistatic agent, and preparation method and application thereof

    CN110922592A